2014
DOI: 10.1111/opo.12148
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive speed of processing training in older adults with visual impairments

Abstract: Purpose: To examine whether older adults with vision impairment differentially benefit from cognitive speed of processing training (SPT) relative to healthy older adults. Methods: Secondary data analyses were conducted from a randomised trial on the effects of SPT among older adults. The effects of vision impairment as indicated by (1) near visual acuity, (2) contrast sensitivity, (3) self-reported cataracts and (4) self-reported other eye conditions (e.g., glaucoma, macular degeneration, diabetic retinopathy,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 66 publications
(108 reference statements)
2
8
0
Order By: Relevance
“…In human studies, substantial changes in speed of processing (SOP) and in other spectro-temporal (or spatiotemporal) signal resolution of performance abilities have been shown to result from attention-demanding, speed-challenged auditory (3,(5)(6)(7) or visual training (8)(9)(10)(11). For example, the accurate behavioral identification and stimulus-order reconstruction of rapidly successive auditory stimuli was restored in human individuals trained in their eighth decade of life to a performance level normally typifying human performance abilities recorded in their third or fourth decade (3,6).…”
mentioning
confidence: 99%
“…In human studies, substantial changes in speed of processing (SOP) and in other spectro-temporal (or spatiotemporal) signal resolution of performance abilities have been shown to result from attention-demanding, speed-challenged auditory (3,(5)(6)(7) or visual training (8)(9)(10)(11). For example, the accurate behavioral identification and stimulus-order reconstruction of rapidly successive auditory stimuli was restored in human individuals trained in their eighth decade of life to a performance level normally typifying human performance abilities recorded in their third or fourth decade (3,6).…”
mentioning
confidence: 99%
“…Older adults had fewer accurate trials reaching to the target than young adults under BOVF (5.762 vs. 10.091, p<.001) condition while no difference was found under POVF condition between the two age groups (20.000 vs. 19.969, p=.971). Additionally, older adults with POVF completed the reaching task more accurately than older adults with BOVF (20.000 vs. 5.762, p<.001).…”
Section: Accurate Numbermentioning
confidence: 84%
“…Ageing-related visual impairments degraded performance in Useful Field of View Test (UFOV). It indicated that older adults would have difficulties to obtain visual information which often manifests as slow cognitive processing speed [19].…”
Section: Introductionmentioning
confidence: 99%
“… 31 However, a limited number of studies have implemented cognitive training interventions specifically in populations with sensory loss. 30 , 32 Consistent with findings from the current study, speed‐of‐processing training was effective in improving cognitive performance (UFOV Test) in both participants with and without impaired near visual acuity or contrast sensitivity. 30 Similarly, Lawrence et al.…”
Section: Discussionmentioning
confidence: 99%